Panduan Obyek Wisata Kabupaten Pacitan Berbasis Android - Nursanti, Diah Asri; , Dr. Ir. Bana Handaga, M.T (2016)
Pacitan Regency is located in East Java province which borders directly with Central Java and Yogyakarta Special Region Province. Pacitan district is an area that is popular with tourists visiting within the natural's tourism be in the form of the caves and coastal tourist destinations. In helping tourists to find out the tourist attractions in Pacitan, we need to develop basic tourist guide with android system. Using the android-based tourist guide, tourists can easily search for more detailed an information about tourist areas in Pacitan. In software development, we use a method of collecting data through analysis needs. Completion of this application includes the design, manufacture, testing, repairing and finishing of the application. Android based software of the Pacitan travel guide isn't only for tourists who want to visit Pacitan but also as the media of Pacitan tourism promotion.